In vitro Anti‐Inflammatory Potency of Sanguinarine and Chelerythrine via Interaction with Glucocorticoid Receptor. Issue 6 (21st January 2021) - Zhang, Jie; Liang, Yuan; Ren, Li; Zhang, Tiehua
Abstract : As quaternary benzo[ c ]phenanthridine alkaloids, sanguinarine and chelerythrine possess multiple biological activities including anti‐inflammatory effects. They have been confirmed to regulate gene expression of inflammatory‐related cytokines at transcription level. This work aims to investigate the glucocorticoid‐like anti‐inflammatory effects of sanguinarine and chelerythrine, which may be mediated by Glucocorticoid Receptor (GR). Firstly, the interactions of GR with sanguinarine and chelerythrine were investigated by fluorescence polarization assay and the result showed that these two alkaloids could bind to GR with potent affinities. Luciferase reporter assay showed that sanguinarine was a weak GR agonist but chelerythrine failed to induce GR transcriptional activation in HeLa cells. These two alkaloids at high concentration showed similar tumor necrosis factor‐ α inhibitory potency to dexamethasone in RAW 264.7 cells, indicating their anti‐inflammatory effects in vitro . In addition, the results of molecular docking and dynamics simulations showed that sanguinarine and chelerythrine could bind effectively with GR and might serve as its functional ligands. In conclusion, chelerythrine was speculated to be a selective GR modulator that might exhibit GR‐mediated beneficial actions with reduced side effects. GRAPHICAL ABSTRACT: